1996
DOI: 10.2134/agronj1996.00021962008800050020x
|View full text |Cite
|
Sign up to set email alerts
|

A Greenhouse Screening Technique for Acid Soil Tolerance in Maize

Abstract: Evaluating maize (Zea mays L.) in the field for tolerance to soil acidity is expensive and provides variable results. To identify alternative screening techniques for maize, the present study adapted a pot bioassay already used for other crops. Two experiments were conducted. One included a set of diallel crosses from eight parents and the other a set of 10 open‐pollinated cultivars. These materials were evaluated under field conditions, in nutrient solution, and in pots containing 2 kg of soil. The best resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 19 publications
2
28
0
Order By: Relevance
“…Moreover, screening at field level is very expensive and time consuming when a large number of genotypes are under evaluation (Garcia et al 1979). Besides, the results obtained with solution culture screening method correlate positively with those obtained using field screening (Urrea-Gomej et al 1996), indicating reliability and dependability of laboratory screening methods.…”
Section: Introductionmentioning
confidence: 60%
“…Moreover, screening at field level is very expensive and time consuming when a large number of genotypes are under evaluation (Garcia et al 1979). Besides, the results obtained with solution culture screening method correlate positively with those obtained using field screening (Urrea-Gomej et al 1996), indicating reliability and dependability of laboratory screening methods.…”
Section: Introductionmentioning
confidence: 60%
“…The high relationship of stressed and unstressed treatments implies that differences among genotypes were largely constitutive. Urrea-Gómez et al (1996) suggested that constitutive morphological characteristics such as vigorous rooting could be advantageous in the breeding of Al-resistant cultivars. One underlying issue that may influence plant response is the initial vigour of the seedlings, reflecting differences in seed size.…”
Section: Discussionmentioning
confidence: 99%
“…Screening and selection for Al tolerance in maize involves field evaluation for more than one cropping season [17]. However, the high coefficient of variation resulting from spatial variation in the soils poses a challenge to field evaluation [17] and eventually affects the reliability of the results.…”
Section: Introductionmentioning
confidence: 99%
“…However, the high coefficient of variation resulting from spatial variation in the soils poses a challenge to field evaluation [17] and eventually affects the reliability of the results. Therefore, laboratory hydroponic studies of root traits offer another option if the laboratory results are correlated to field performance under the same stress conditions [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation